Novel intercalated CuO/black phosphorus nanocomposites: Fabrication, characterization and NO2 gas sensing at room temperature. (May 2020) - Wang, Yang; Xue, Jialing; Zhang, Xueyi; Si, Jiaqi; Liu, Yang; Ma, Laifeng; ullah, Mohib; Ikram, Muhammad; Li, Li; Shi, Keying
Abstract: In this paper, intercalated CuO/BP nanocomposites (NCPs), with small and extremely dispersed CuO nanoparticles (NPs) on pyrrole (Py)-modified expanded black phosphorus (BP) nanosheets (NSs), were synthesized by a simple hydrothermal method. In the synthesis process, the expanded BP is first expanded with diethylene glycol dimethyl ether, and then following CuO NPs growth, the Cu(CH3 COO)2 ·H2 O precursor is completely injected into the middle layer of the Py modified expanded BP NSs (Py-EBP) under vacuum. The CuO/BP NCP inserted under hydrothermal conditions is formed in situ in the intermediate layer of the Py-EBP NSs. Intercalating CuO/BP-190 NCP with 4–5 nm CuO NPs for 5 h at 190 ° C yields a high sensitivity of 20.7, rapid response of 4 s, superior selectivity and wide range of target NO2 gas sensing from 100 ppm to 10 ppb at room temperature (RT) in air. Therefore, the method developed in this work is of great significance for easy synthesis and large-scale production of stable CuO/BP NCP and has great prospects for applications in gas sensors. Graphical abstract: CuO/BP composite was synthesized by a facile route in situ growth of small sized CuO nanoparticles in the interlayers of expanded BP, which was functionalized by Py and formed the air-stable overlayers and stacking effect; The CuO/BP-190 sensor exhibited superior gas sensing property: response of 20.7 with fast response of 4 s–100 ppm NO2, the lower detection limit reached 10 ppb at room temperature. Image 1 Highlights: For CuO/BP-190 composite, functionalized Py formed the air-stable overlayers and stacking effect with EBP. BP NSs overlapped with CuO nanoparticles, formed heterojunctions, which can act as channels for electron transportation. The CuO/BP-190 sensor exhibited superior gas sensing property at room temperature, Such as, response of 20.7 with fast response of 4 s–100 ppm NO2, the lower detection limit reached 10 ppb.